Quantification of differences between occupancy and total monitoring periods for better assessment of exposure to particles in indoor environments. (April 2015) - Wierzbicka, A.; Bohgard, M.; Pagels, J.H.; Dahl, A.; Löndahl, J.; Hussein, T.; Swietlicki, E.; Gudmundsson, A.
Abstract: For the assessment of personal exposure, information about the concentration of pollutants when people are in given indoor environments (occupancy time) are of prime importance. However this kind of data frequently is not reported. The aim of this study was to assess differences in particle characteristics between occupancy time and the total monitoring period, with the latter being the most frequently used averaging time in the published data. Seven indoor environments were selected in Sweden and Finland: an apartment, two houses, two schools, a supermarket, and a restaurant. They were assessed for particle number and mass concentrations and number size distributions. The measurements using a Scanning Mobility Particle Sizer and two photometers were conducted for seven consecutive days during winter in each location. Particle concentrations in residences and schools were, as expected, the highest during occupancy time. In the apartment average and median PM2.5 mass concentrations during the occupancy time were 29% and 17% higher, respectively compared to total monitoring period. In both schools, the average and medium values of the PM2.5 mass concentrations were on average higher during teaching hours compared to the total monitoring period by 16% and 32%, respectively. When it comes to particle number concentrations (PNC), in the apartment during occupancy, the average and median values were 33% and 58% higher, respectively than during the total monitoring period. In both houses and schools the average and median PNC were similar for the occupancy and total monitoring periods. General conclusions on the basis of measurements in the limited number of indoor environments cannot be drawn. However the results confirm a strong dependence on type and frequency of indoor activities that generate particles and site specificity. The results also indicate that the exclusion of data series during non-occupancy periods can improve the estimates of particle concentrations and characteristics suitable for exposure assessment, which is crucial for estimating health effects in epidemiological and toxicological studies. Highlights: Only the concentrations from occupancy periods should be used for the exposure assessment. Inclusion of non-occupancy data for exposure assessment underestimated the PM2.5 mass concentrations in residences and schools. PNC indoors varied to a great degree in residences and was influenced by indoor activities and site specificity. In an apartment, the median PNC was 58% higher during occupancy time than during total monitoring period.